2023
DOI: 10.1039/d2cy01563c
|View full text |Cite
|
Sign up to set email alerts
|

Propane oxidative dehydrogenation using CO2 over CrOx/Fe–CeO2 catalysts

Abstract: The kinetic behavior of CrOx sites supported on Fe doped CeO2 was studied for the CO2-assissted propane oxidative dehydrogenation. The support was synthesized via a co-precipitation method of Fe and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Therefore, a C 3 H 8 /CO 2 ratio of no lower than 0.6 was recommended to improve the olefin yield and catalyst lifetime. Wang et al 101 found that at relatively lower temperatures and CO 2 /C 3 H 8 ratios, selective dehydrogenation pathways are kinetically more favorable over 3 wt% CrO x /10Fe-CeO 2 , where Cr-O and CrO can be regarded as surface oxygen sites for propane adsorption, and then the generated oxygen defects/vacancies are replenished by CO 2 . In addition, they found that the rate of propane consumption tends to be unaffected by CO 2 , but the rate of propene formation decreases monotonically with an increase in CO 2 , which indicates that propane dry reforming become favorable under high CO 2 /C 3 H 8 conditions.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a C 3 H 8 /CO 2 ratio of no lower than 0.6 was recommended to improve the olefin yield and catalyst lifetime. Wang et al 101 found that at relatively lower temperatures and CO 2 /C 3 H 8 ratios, selective dehydrogenation pathways are kinetically more favorable over 3 wt% CrO x /10Fe-CeO 2 , where Cr-O and CrO can be regarded as surface oxygen sites for propane adsorption, and then the generated oxygen defects/vacancies are replenished by CO 2 . In addition, they found that the rate of propane consumption tends to be unaffected by CO 2 , but the rate of propene formation decreases monotonically with an increase in CO 2 , which indicates that propane dry reforming become favorable under high CO 2 /C 3 H 8 conditions.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…6). Wang et al 101 found that the incorporation of trivalent Fe in the CeO 2 support facilitated the generation of more active lattice oxygen, which could react with hydrocarbon species (CH x ) and help to reduce the possibility of atomic carbon formation and enhance the stability of Cr/Fe–CeO 2 catalysts in CO 2 -OPDH (Table 2).…”
Section: Metal Oxide-based Catalystsmentioning
confidence: 99%
“…Overall, the initial values of propane and CO2 conversions in combination with the propylene selectivities are at a higher level than those of other VOx-based catalyst systems, [23][24][25]27 and even reach those of some of the supported CrOx systems. 18,21,40 Figures 2b and c depict the time-dependent conversions of C3H8 and CO2 for the P25-based samples. As shown in Figure 2b, the propane conversion is significantly higher at the beginning of the reaction, which is most pronounced for the samples loaded with 1.2 and 2.5 V/nm².…”
Section: Reactivity Behavior and Analysis Of The Reaction Networkmentioning
confidence: 99%
“…[14][15][16][17] In the past, a research focus was put on chromium oxide (CrOx) due to its high activity. 7,[18][19][20][21] In this context, Mychorczyk et al 20 described the oxidation state of chromium, as measured via operando UV-Vis spectroscopy, to be of great importance to differentiate between the oxidative and nonoxidative reaction paths, where Cr 6+ species are reduced rapidly to Cr 2+/3+ species under reaction conditions, which participate in the non-oxidative pathway. However, as chromium oxides are toxic and harmful to the environment, other materials have attracted renewed interest.…”
Section: Introductionmentioning
confidence: 99%